The Effect of Problem-Based Learning Models on Students' Self-Efficacy in Excretion System Material at SMA - Farida Romandani; Ika Sukmawati; Muhammad Radian Nur Alamsyah (Jurnal Pendidikan Biologi, 2023)
The background of this research is the lack of self-efficacy in students and the learning model used by teachers.. The purpose of this study was to determine the effect of the problem-based learning model on the self-efficacy of SMA Negeri 2 Grabag students on excretion system materials. This research is a quasi-experimental study with a non-equivalent control group design. The population in this study were students of class XI MIPA 3 and XI MIPA 4 for the 2022/2023 academic year. The sample in this study used two classes from the population class which were used as the control class and the experimental class which were determined using a purposive sampling technique. The data obtained were analyzed using the Mann-Whitney u-test and the independent t test at a significance level of ∝ =0.05, and analyzed with the help of the SPSS program. The results showed that the average initial self-efficacy score of 68.86 experienced an increase in the final average self-efficacy score of 79.43 with an average of 10.57% with the influence of problem-based learning models. Based on research results problem-based learning models can be used as an alternative learning model to improve student self-efficacy. Teachers need to be more active in order to be able to develop learning models that are implemented, so as to increase self-efficacy in students.